Refugee Welfare : A Global Public Good - Mottaghi, Lili (World Bank, Washington, DC, 2018)
This brief discusses about the refugees welfare in Middle East and North Africa (MENA). Refugee flows can significantly alter the social and economic fabric of host communities, with the impact depending on initial conditions in labor markets, access to resources, demographics, labor laws, and the policy responses of host governments. Most refugees are concentrated in relatively fragile countries, many relatively small and economically vulnerable, including Kenya, Lebanon, and Jordan. To recognize the global public good that Lebanon and Jordan provided by opening their borders to Syrian refugees, in April 2016, the World Bank, the United Nations, and Islamic Development Bank, in close collaboration with the donor community and a range of international partners, launched the Concessional Financing Facility (CFF). The CFF focused on helping Jordan and Lebanon address the impact of Syrian refugees without having to increase their debt levels. As of April 2018, the renamed Global Concessional Financing Facility (GCFF) has leveraged concessional financing to Lebanon and Jordan for ten projects.